2001
DOI: 10.1038/89675
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The SAND domain is a conserved sequence motif found in a number of nuclear proteins, including the Sp100 family and NUDR. These are thought to play important roles in chromatin-dependent transcriptional regulation and are linked to many diseases. We have determined the three-dimensional (3D) structure of the SAND domain from Sp100b. The structure represents a novel alpha/beta fold, in which a conserved KDWK sequence motif is found within an alpha-helical, positively charged surface patch. For NUDR, the SAND do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(97 citation statements)
references
References 38 publications
3
94
0
Order By: Relevance
“…In the folded form, both the HSR and the leucine zipper domains are available for molecular interaction. A recent determination of the three-dimensional structure of the SAND domain from Sp100b represented a novel ␣/␤-fold, in which a conserved KDWK sequence motif is found within an ␣-helical, positively charged surface patch (20). In our model for AIRE, the proposed DNA binding SAND and the known DNA binding zinc finger domains are also exposed for DNA-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the folded form, both the HSR and the leucine zipper domains are available for molecular interaction. A recent determination of the three-dimensional structure of the SAND domain from Sp100b represented a novel ␣/␤-fold, in which a conserved KDWK sequence motif is found within an ␣-helical, positively charged surface patch (20). In our model for AIRE, the proposed DNA binding SAND and the known DNA binding zinc finger domains are also exposed for DNA-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The B834 cells were grown in M9 medium supplemented with all natural amino acids except methionine, plus 50 mg/liter selenomethionine. Proteins were first purified by Ni 2ϩ affinity chromatography, as described previously (33). The His 6 tag was removed by incubation at 23°C with tobacco etch virus protease.…”
Section: Methodsmentioning
confidence: 99%
“…A Second Self-interacting Region Occurs in the DEAF-1 SAND Domain-Gel chromatography had previously indicated that the DEAF-1 SAND domain may dimerize (24). To confirm this interaction and to further define the interacting motifs, GST fusion proteins with full-length DEAF-1 (GST-(1-565)) and a region containing the SAND domain (GST-(173-375)) were incubated with radiolabeled full-length DEAF-1 (Fig.…”
Section: Fig 5 the Deaf-1 Sand Zinc Binding Motif And Nls Region mentioning
confidence: 99%
“…A fusion protein between GST and amino acids 167-370 of DEAF-1 (peptide J, GST-167-370) was previously shown to bind a DNA ligand that contained two TTCG elements spaced apart by 9 base pairs (N52-69 probe), and mutation of the CG residue(s) in a single TTCG element (Mut 1) or in both TTCG elements (Mut 2) eliminated DNA binding (24). In addition, the shorter SAND domain (187-324) had previously bound the N52-69 probe as both a low and a high mobility species, and was also able to bind the Mut 1 probe but not the Mut 2 probe (24).…”
Section: Fig 5 the Deaf-1 Sand Zinc Binding Motif And Nls Region mentioning
confidence: 99%
See 1 more Smart Citation